2015
DOI: 10.14573/altex.1506201
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity testing in the 21st century beyond environmental chemicals

Abstract: Summary After the publication of the report titled Toxicity Testing in the 21 st Century – A Vision and a Strategy , many initiatives started to foster a major paradigm shift for toxicity testing – from apical endpoints in animal-based tests to mechanistic endpoints through delineation of pathways of toxicity (PoT) in human cell based systems. The US EPA has funded an important project to develop new high throughput technologies based on human cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 47 publications
0
66
0
1
Order By: Relevance
“…In the case of the pharmaceutical industry, the situation is quite different (Rovida et al, 2015). Firstly, testing the safety and efficacy of drugs and related products before entering first clinical trials in man is not only ethically accepted, but even legally requested.…”
Section: Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the pharmaceutical industry, the situation is quite different (Rovida et al, 2015). Firstly, testing the safety and efficacy of drugs and related products before entering first clinical trials in man is not only ethically accepted, but even legally requested.…”
Section: Acceptancementioning
confidence: 99%
“…In contrast, the pharmaceutical industry, interested in new drugs and related products, is obliged to demonstrate not only product safety, but also efficacy (Rovida et al, 2015). This includes providing evidence that an active pharmaceutical ingredient (API) becomes biologically available at its intended site of action (e.g., inner organ, tissue, cell or receptor), meaning that it is able to cross relevant absorption barriers which otherwise would limit its bioavailability and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The website of the Balanced Scoreboard Institute 2 and Strategy Management Group 3 , two consultancies for organizations in strategic planning, define: "Strategic planning is an organizational management activity that is used to set priorities, focus energy and resources, strengthen though harmonized via the International Conference on Harmonization 9 , as the US, which has 6% of the world population, consumes about 60% of drugs under patent, which gives them a lighthouse function for the pharmaceutical industry (Rovida et al, 2015a Wambaugh et al, 2015), ToxCast (Richard et al, 2016), the Tox 21 collaboration with the NIH and the FDA, the Virtual Tissues 5 and computation toxicology in general (Patlewicz and Fitzpatrick, 2016) It promotes mechanism-based toxicity testing and risk assessment according to the principles laid down for toxicology for Tox21. The project will integrate advances in in vitro and in silico toxicology, read-across methods, and adverse outcome pathways.…”
Section: Strategic Planning In Toxicologymentioning
confidence: 99%
“…8,9,12,13,14,15 Actually, studies have assessed the in vitro cytocompatibility of Biodentine using immortalized cell lineages of different tissues or mammal origins, including three-dimensional spheroid pulp cell culture 15 or osteosarcoma cells, 12,13 with interesting results pointing to the biocompatibility of this material, indicating its capacity to induce proliferation and mineralization in vitro. 13 Nevertheless, these results still require some level of extrapolation either from animal-to-human models, whose limitations have been constantly discussed in light of the 21 st century toxicology paradigms, 16 or extrapolation from aneuploid/immortalized cell lineages to the unaltered primary human cells found in healthy tissues. In this regard, studies 17,18 have confirmed that, even though many similarities might be found between human primary cells and the main studied osteoblast-like cell lines, such as MC3T3, MG63, or SAOS2, differences in their response to biomaterials point to the importance of primary cell studies.…”
Section: Discussionmentioning
confidence: 99%